Understanding multi-scale ion-transport in solid-state lithium batteries - Wen Yu; Nanping Deng; Yang Feng; Xiaofan Feng; Hengying Xiang; Lu Gao; Bowen Cheng; Weimin Kang; Kai Zhang (eScience)
Solid-state lithium battery (SSLB) is considered as one of the promising candidates for next-generation power batteries due to high safety, unprecedented energy density and favorable adaptability to high pression and temperature. However, the system of solid electrolyte (SE), as one of the most important components in SSLB, is usually plagued by clumsy ionic transport, leading to poor rate performance of the SSLBs. Herein, a unique perspective is proposed to re-examine the ion-transport behavior in lithium conductors by tracing Li+ at multi-scale, including microscopic, mesoscopic and macroscopic scales. The multi-scale ion-transport mechanisms and corresponding characterization techniques are analyzed in depth. Furthermore, some strategies of structure design to improve ion-transport kinetics at corresponding scales are elaborated systematically, involving the modulation of microscopic homogeneous structure, mesoscopic heterogeneous structure and macroscopic structures, etc. The proposed generalized rules for SEs are expected to construct a close link from mechanism−structure−characterization to high performances for SSLBs.